Hashtag Black Lives Matter’s Tweets as Education Media Messages - Rahmanita Zakaria; Delfia Herwanis; Sylvia Kinanti (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
TThe objectives of this study are to discover the various types of and the most frequently presuppositions used in the hashtag black lives matter's tweets as the education media messages on Twitter anchoring in Yule's theory of presupposition. This research employs a descriptive qualitative approach to elucidate and comprehend the meaning of utterance words in individuals or groups associated with a social or human problem. The analysis of the data used both qualitative and quantitative methods. The researcher discovered that existential presuppositions are the most frequently used type of presupposition in hashtag black lives matter's tweets, accounting for 41%. The factive presupposition is the second most frequently used type, accounting for 26 %. The lexical presupposition is the third most frequently used type of presupposition, accounting for 24%. The fourth position is occupied by the structural presupposition, which contains 11 data points out of 100 (8%), and the final position is occupied by the counterfactual presupposition, which contains one data 0,75%. This hashtag teaches law enforcement officers to investigate legal cases before imposing punishment.